The European heritage - Delanty, Gerard, author.
1 online resource
Keywords: "Gerard Delanty offers a critical interpretation of the European heritage today in light of recent developments in the human and social sciences, and in view of a mood of crisis in Europe that compels us to re-think the European past. One of the main insights informing this book is that a transnational and global perspective on European history can reorient the European heritage in a direction that offers a more viable way for contemporary Europe to articulate an intercultural identity in keeping with the emerging shape of Europe, and with its own often acknowledged past. He argues that the European heritage is based less on a universalistic conception of culture than on a plurality of interconnecting narratives, and the inclusion of new voices and is being forged in new spaces of critical dialogue. Such a perspective opens up new directions for scholarship and public debate on heritage that are guided by critical cosmopolitan considerations that highlight contention, resistances, competition and dissonance. He argues that the specificity of the European dimension of culture is in the entanglement of many cultures rather than in an original culture. The cultures of Europe are not separated but have been shaped in close interaction with each other and with the non-European world. Nations are not therefore unique, exceptional or fundamentally different from each other. The outcome of such intermingling is a multiplicity of ideas of Europe that serve as shared cultural reference points"--Provided by publisher.